Menurunkan Stres Kerja Petugas Pemasyarakatan melalui Teknik COPE - Unika Prihatsanti; Ika Zenita Ratnaningsih; Anggun Resdasari Prasetyo (Jurnal Psikologi, 2013)
This research aimed to examine the effectiveness of coping technique in reducing working stress. The reduced level of stress was expected to make more optimal performance. Subject consisted of 20 correctional officers, which were divided into two groups. 10 officers were in experimental group, which were trained with coping technique, and the other ten belonged to control group. The research used quasi-experimental design with control group that was untreated at pretest-posttest. Working stress was measured with a scale in which each subject in both groups filled the work stress scale before and after treatment. Data analysis using the Mann Whitney U- test indicated that there was a significant effect of the application of coping technique as an alternative solution to reduce the level of working stress of the correctional officers (U=20.00; p=0.023